2007
DOI: 10.1149/1.2734875
|View full text |Cite
|
Sign up to set email alerts
|

Study of Thermal Stability of HfO[sub x]N[sub y]∕Ge Capacitors Using Postdeposition Annealing and NH[sub 3] Plasma Pretreatment

Abstract: We studied the thermal stability of the as-deposited HfO x N y thin films on the Ge substrate by employing rapid thermal annealing. After undergoing high-temperature processing, we observed several interesting physical and electrical features presented in the HfO x N y /Ge system, including a large Ge out-diffusion ͑Ͼ15 atom %͒ into high-k films, positive shift of the flatband voltage, severe charge trapping, and increased leakage current. These phenomena are closely related to the existence of GeO x defective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…It has been experimentally observed that the outdiffusion 5 of Ge in channel will cause the degradation of gate dielectrics such as positive flatband voltage shift, 6-9 gate leakage current, [8][9][10] and hysteresis 8 enlargement. However, the mechanism for the degradation of Ge contaminated highk dielectrics is not clear yet.…”
Section: Impact Of Germanium Related Defects On Electrical Performancmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been experimentally observed that the outdiffusion 5 of Ge in channel will cause the degradation of gate dielectrics such as positive flatband voltage shift, 6-9 gate leakage current, [8][9][10] and hysteresis 8 enlargement. However, the mechanism for the degradation of Ge contaminated highk dielectrics is not clear yet.…”
Section: Impact Of Germanium Related Defects On Electrical Performancmentioning
confidence: 99%
“…Let us consider the Ge contaminated HfO 2 with n-type substrate and low work function metal gate ͑TaN, most well studied 6,7,9 ͒. According to the secondary ion mass spectroscopy analysis reported in previous publication, 5,8 Ge tends to pileup at the two interfaces of MOS capacitor ͑U shape͒. The ECP at the top interface ͑metal/oxide͒ is determined by the work function of the metal gate.…”
Section: Impact Of Germanium Related Defects On Electrical Performancmentioning
confidence: 99%
“…It has been demonstrated in many reported literatures that the GeO 2 degradation during the annealing will cause the positive V fb shift. The desorption process of Ge-O is believed to generate additional negative charges [28, 29]. Therefore, it can also be concluded that GeO 2 decomposition is suppressed by Ge-O-Si interlayer from V fb shift.…”
Section: Resultsmentioning
confidence: 99%
“…The nitridation of Ge surfaces prior to high-k film deposition is one of the best-known solutions because it is effective in suppressing Ge diffusion in metal oxides and leads to improved performance of Ge-based devices. [4][5][6][7][8][9][10][11] Annealing in NH 3 ambient is widely used for Ge surface nitridation and the formation of the GeON interface layer. [6][7][8][9][10] However, these methods for introducing the nitrogen element always involve high-temperature treatment above 550 °C.…”
Section: Introductionmentioning
confidence: 99%